Types of hemodynamic response to orthostasis according to continuous blood pressure monitoring: a case series of heart failure with reduced ejection fraction - D. N. Fedorova; A. E. Solovieva; V. L. Galenko; A. V. Kozlenok; A. V. Berezina; S. V. Villevalde (Российский кардиологический журнал)
Heart failure (HF) is associated with unfavorable outcomes and high health care costs. Determination of the hemodynamic response to orthostasis can be an additional tool in assessing the stability and compensation of HF patients. Active orthostatic test (AOT) with blood pressure monitoring serves as a simple and available screening method. However, a complete characteristic of the hemodynamic response, especially during the first minute of orthostasis, can be obtained only with continuous blood pressure monitoring. The presented case series demonstrate the types of hemodynamic response in patients with heart failure with reduced ejection fraction in AOT with continuous blood pressure monitoring, available data on the mechanisms of its development, clinical and prognostic role, and also presents the advantages and limitations of AOT.